Linguistics and Philology—Separate, Overlapping or Subordinate/Superordinate Disciplines? Linguistic and Philological Perspectives: Papers forming part of the 2017 and 2018 SBL Linguistics and Biblical Hebrew Seminar - Naudé, Jacobus A.; Miller-Naudé , Cynthia (Journal for Semitics, 2021)
In this paper, we explore arguments concerning the disciplinarity of linguistics and philology as fields of academic knowledge. We begin with a brief historical overview of philology and linguistics. We then consider the question of whether linguistics and philology in the twenty-first century should be viewed as separate disciplines or as overlapping disciplines, or whether one discipline—philology—should be viewed as a superordinate discipline which subsumes linguistics.